Early treatment with UR13870, a novel inhibitor of p38α mitogenous activated protein kinase, prevents hyperreflexia and anxiety behaviors, in the spared nerve injury model of neuropathic pain. (14th September 2015) - Galan-Arriero, Iriana; Avila-Martin, Gerardo; Ferrer-Donato, Agueda; Gomez-Soriano, Julio; Piazza, Stefano; Taylor, Julian
Highlights: Microglial cell inhibition, through p38α MAPK, is a potential treatment for neuropathic pain. UR13870 is a highly specific p38α inhibitor. UR13870 prevents thermal and mechanical hyperreflexia and open field anxiety in the SNI model. UR13870 inhibits microglial reactivity within the lumbar dorsal horn after SNI. Abstract: Microglia cell activation plays a role in the development of neuropathic pain partly due to the activation of the p38α MAPK signaling pathway after nerve injury. In this study we assessed the effect of UR13870, a p38α MAPK inhibitor, in the "spared nerve injury" (SNI) model, to study its effects on modulation of spinal microglial activation and to test behavioral hyperreflexia responses and cerebral-mediated pain behavior. The effect of daily administration of UR13870 (10 mg/kg p.o.) and Pregabalin (50 mg/kg p.o.) on reflex hypersensitivity to mechanical and cold test stimuli and on affective related pain responses measured with the place escape avoidance paradigm and the open field-induced anxiety test, were evaluated after SNI in Sprague Dawley rats. Microglial reactivity in the ipsilateral lumbar laminae I/II dorsal horn was evaluated with OX-42 immunohistochemistry. UR13870 treatment significantly decreased hindlimb hyperreflexia to both mechanical and cold stimuli after SNI without loss of general motor function, in addition to a reduction in pain-related anxiety behavior at day 21 after SNI, accompanied by normalization of OX-42 immunoreactivity within the ipsilateral lumbar dorsal horn. Pregabalin treatment only reduced mechanical hyperreflexia and affected general motor function. Oral administration of the p38α MAPK inhibitor, UR13870, mediates antinociception to both mechanical and cold stimuli, and significantly restored inner-zone exploration in the open field test, accompanied by normalization in dorsal horn microglial activation in the SNI model.